Modern tactics for acute variceal bleeding in liver cirrhosis (Baveno VII guidelines) - S. M. Chooklin; S. S. Chuklin (Клінічна хірургія)
Modern tactics for acute variceal bleeding in liver cirrhosis (Baveno VII guidelines)